An examination of the ways in which the five case study departments of the Provincial Government of the Western Cape have organised their monitoring and evaluation function - Cwayi, Siphumeze (Department of Political Studies, 2015)
This study looks at five departments in the Provincial Government of the Western Cape as case studies and examines the ways in which they have organized their M&E [monitoring and evaluation] function.